1218 Sharing videos and annotated pictures to improve family centred care – an essential adjunct?. (17th August 2022) - Fisher, Lesley; Patel, Neil; Trobe, Simon; Kidson, Chris
Abstract : Aims: We describe our experience of using 'vCreate', an NHS-approved secure cloud based technology that allows healthcare professionals to share videos and annotated images with absent carers, on our regional paediatric intensive care unit (PICU). For most families, 'what matters to me' is respecting the virtues of 'family centred care', a philosophy that we believe is strengthened by the 'vCreate' system. Methods: The 'vCreate' system is well established in our neonatal intensive care unit (NICU) and in many NICUs throughout the country. Following a period of comprehensive preparation we secured Governance and Informational Technology approval to launch in 2018. The service rapidly gained internal prestigious repute. Video/images are captured onto dedicated unit tablets and up-loaded directly onto the carer's account using the 'vCreate' web-app. Carers receive an alert inviting them to log into their account to view and/or download the most recent post. There is no restriction on timing or number of entries but we included a 90 day deletion policy. The content is purely non-clinical as the aim is to capture special moments to be included within a patient diary. We report our cumulative experience. Results: The system is offered to all patient carers. 7929 pictures and 1037 videos have been sent to 671 families. 11 nursing 'superstars' have been nominated by the carers and repeated nominations allowed us to award a PICU superstar of the year award. We collate feedback for quality assurance monitoring and report the most recent family quotes: '[the image] to say goodnight … was so reassuring to know she was settled with her nurse'; 'meant the world to us'; 'ease some of the guilt and pain and made us still feel part of their journey'. And key comments made by staff: 'key service that we have been lucky enough to provide … reassurance they (carers) need … ensures that no parent misses out on a PICU milestone'; 'integrated into my daily role … families telling you how a certain photograph made them feel is heart-warming'; 'happy to bring joy to families in stressful and worrying times'; 'few minutes of my time makes a huge difference to families'; 'vital in supporting parents and families and they really do appreciate this amazing service'. Conclusion: The 'vCreate' system is feasible, greatly valued and is embedded within our clinical practice. We noted an increase in usage during the pandemic and our key staff were pivotal to introducing the service into adult intensive care units around the city. Key personnel won the 'Scottish Health Award – Innovation Award 2021'. We raise the possibility that equivalent benefits could be appreciated by carers who cannot reside with their baby/child admitted to the general paediatric or neonatal wards. As 'vCreate' is transferable, a patient's convalescence on the general paediatric/neonatal ward following discharge from PICU/NICU can be added to their diary.